Experimental and numerical study of tantalum‑tungsten alloy rod penetrator impacting thick armor plate. (September 2022) - Cheng, Chun; Fu, Yingqian; Du, Chengxin; Du, Zhonghua; Jiang, Zhaoxiu; Zhou, Feng; Zhong, Kun; Wang, Xiaodong
Abstract: To study the penetration ability of tantalum‑tungsten alloy rod penetrator into armor plate and clarify its deformation and failure behavior in the process of penetration, the experimental and numerical study of tantalum‑tungsten alloy rod penetrator penetrating armor plate was carried out in this paper. The results show that the penetration efficiency of tantalum‑tungsten alloy rod penetrator and tungsten alloy rod penetrator into 30CrMnMoRE armor plate is equivalent in the range of impact velocity from 1100 m/s to 1700 m/s, whereas the penetration efficiency per unit specific kinetic energy of tantalum‑tungsten alloy rod penetrator is higher than that of tungsten alloy rod penetrator when the impact velocity is greater than 1500 m/s. The ultimate penetration velocity of tantalum‑tungsten alloy rod penetrator with length-to-diameter ratio of 6.25 and diameter of 8 mm to 30CrMnMoRE armor plate with the thickness of 60 mm is about 1695 m/s. At the moment of impacting the target plate, the velocity of the head of the tantalum‑tungsten alloy rod penetrator decreases sharply, but the velocity at the rear of the penetrator remains basically unchanged. In the process of penetration, the head of the penetrator deforms and flows outward under the huge impact pressure, and finally, the length of the penetrator is shortened to zero, forming a barrel-like structure, but the barrel structure still has a certain penetration ability. This study can help to further understand the flow characteristics and penetration ability of tantalum‑tungsten alloy rod penetrator in high-speed penetration. Highlights: The penetration efficiency of tantalum tungsten alloy rod penetrator and the deformation and flow behavior of it during penetration process were studied by experiments and numerical simulation. The penetration efficiency per unit specific kinetic energy of tantalum-tungsten alloy rod penetrator was compared with that of tungsten alloy rod penetrator. The velocity variation process at different positions on the penetrator was obtained by numerical simulation.